Konsep Pendidikan Islam: Rasulullah Sebagai Role Model Pendidik - ilmah, Nurul; hannang, Risnawati (PILAR, 2023)
This research aims to find out how Rasulullah Saw's concept of education is in education. This research uses literature study research which examines various books and journals as references that are relevant to the author's research. The type of data used is secondary data, namely data obtained indirectly. The data required in this research was taken from documents related to the research. The data analysis technique used is qualitative analysis. The results of this research show that the concept of Rasulullah Saw's education is: Educating using the question and answer method, Educating with affection and gentleness, Educating with existing events and happenings and Educating with examples and similarities.Keywords: Education; Rasulullah;Educator